Swyer-James syndrome in a 7-year-old female - Jun Mori; Daisuke Kaneda; Atsushi Fujiki; Kenichi Isoda; Tomoya Kotani; Yo Ushijima (MDPI AG, 2016)
Swyer-James syndrome is a rare syndrome that occurs as a result of repeated bronchiolitis and pneumonitis in childhood. Most cases are asymptomatic, and subsequent diagnosis may not occur until adulthood. We present the case of a 7-year-old female with Swyer-James syndrome, which was initially diagnosed and treated as asthma. The patient developed respiratory distress and atelectasis which were treated with biphasic cuirass ventilation. This case suggests that Swyer-James syndrome should be a concern in patients with chronic cough and wheezing, and highlights the importance of taking a careful history and appropriate radiological investigations for diagnosis. Once Swyer-James syndrome is diagnosed, prophylaxis and appropriate management of respiratory infections becomes important.